Respiratory physiotherapy in patients with cystic fibrosis and upper limb deep vein thrombosis. Issue 6 (8th April 2022) - Israeli, Tomer; Eisenstadt, Iris; Shoseyov, David; Armoni, Shoshana; Gileles‐Hillel, Alex; Cremisi, Galit; Cohen‐Cymberknoh, Malena; Breuer, Oded
Abstract: We report physiotherapy management of two patients with severe cystic fibrosis (CF) lung disease and upper limb deep vein thrombosis (DVT). These patients were admitted due to a pulmonary exacerbation. Following peripherally inserted central catheters, they were diagnosed with an upper limb DVT. Due to their underlying lung disease, physiotherapy was mandatory for improvement. However, the DVT and anticoagulation treatment raised concerns for pulmonary emboli and hemoptysis. A framework for physiotherapy management in these patients, using a set of precautions and restrictions to maintain airway clearance while minimizing the risk for pulmonary emboli and hemoptysis, was established. Using this set of instructions, the patients experienced no major adverse events while maintaining sufficient airway clearance to allow respiratory improvement. These precautions were continued until the upper limb DVTs were resolved. To our knowledge, there are currently no guidelines or expert opinions available. Therefore, this framework can help guide physiotherapy management